A Novel Approach to Enhance the Accuracy of Network Topology Optimization. Issue 2 (20th January 2017) - Cho, Yoon-Sung
Abstract: This article describes a fast and efficient method for enhancing the accuracy and speed of topology processing for energy management systems and substation automation systems, one that determines the optimal path for normal and contingency conditions. As the topology and model errors are critical to the quality of state estimation, the proposed method can provide a very good benefit by facilitating operators' recognition of topology errors and enhancing the speed of contingency topology processing. The proposed method can determine the state of network components using a new updating method and identify the topology and measurement errors. In order to detect and identify the topology errors, approaches based on a heuristic method such as using bus mismatches, inconsistency checks, pseudo measurements, and coherency checks are proposed. In addition, topological connectivity for contingency analysis is used to evaluate the effects of breaker status changes specified in a contingency list. To verify the performance of the proposed method, we performed topology determination tests with practical scenarios based on an energy management system. The results of these comprehensive tests show that the proposed method can determine the connectivity of large-scale power systems and can be applied to energy management systems and substation automation systems.